Teachers Quality and Business Education Students Entreprenuerial Skills Development in Public Universities in South West, Nigeria - Ore, Elizabeth Remilekun; Sofolahan, Victoria O.; Owodunni, Pedetin Rebecca (PT ARRUS Intelektual Indonesia, 2025)
This study examined the impact of teacher quality on Business Education students’ entrepreneurship skills development in public universities in Southwest, Nigeria. The study examined the extent to which teacher quality has helped to build students entrepreneurship skills. Two hypotheses were formulated and tested at 0.05 level of significance. Descriptive survey research design method was adopted for the study. The population of the study was 100 to 400 level Business Education students from 11 public universities in Southwest offering Business Education as a course of study and multi-stage sampling technique was adopted to draw the sample size. Firstly, simple random sampling technique was adopted to select four universities from the population of study while purposive sampling technique was used to draw the sample size of 400 participants from the population. A four rating structured online questionnaire titled “Teacher Quality and Business Education Students Entrepreneurial Skills Development Questionnaire” (TQBESESDQ) was employed to gather data for the study. Person Product Moment Correlation (r) was used to test the hypotheses. Results from the findings revealed among others that instructional methods adopted by teachers have a great effect on the development of students’ entrepreneurship skills. Based on the findings, the study recommended that instructional methods adopted by teachers should be tailored towards improving self-reliance skills of students, teachers should be constantly trained and more qualified teachers should be employed in order to meet students’ needs.